Phytochemistry and antibacterial activity of plants extracts compared with two commercial antibiotics against E coli responsible for avian colibacillosis in Benin - Philippe Sessou,; Bruno Ayaovi Yaovi,; Mahudro Yovo,; Judicaël Gamedjo,; François Dossa,; Oscar Nestor Aguidissou,; Kadoeito Cyrille Boko,; Guy Alitonou,; Souaïbou Farougou,; Dominique Sohounhloue, (International Journal of Phytomedicine, 2018)
Despite its prominent place in development strategies, poultry breeding faces many constraints, including pathological ones. Among pathologies that affect poultry, colibacillosis is one of the most diseases that are communicable to humans and associated with heavy economic losses. To fight efficiently against avian colibacillosis, the work aimed to evaluate antimicrobial potential evaluation of non-volatile extracts of Euphorbia hirta and Psidium guajava, as well as the essential oils of Clausena anisata and Aeollanthus pubescens extracts and two commercial antibiotics namely tetracolivit and Oxytetracyclin against Escherichia coli. To achieve this goal, susceptibility tests were performed on a strain of E. coli using agar diffusion and microdilution methods. Results obtained showed that essential oils from Clausena anisata and non-volatile extracts tested were not active on E coli. However, the essential oils extracted from Aeollanthus pubescens were active on the E. coli with MIC of 0.44 ± 0.21 mg/ml and MBC of 0.87 ± 0.41mg / ml for the oil of the whole part, followed respectively by flower oil (MBC = 0.99 mg/ml) and leaf stem oil (MBC= 1.62 mg / ml). Comparing the activity of the essential oils of Aeollanthus with antibiotics tested, we noticed that tetracolivit was more active with MBC =0.15±0.07mg/ml on E. coli than these extracts which were more active than Oxytetracyclin (MBC=2.34±1.11mg/ml). In sum, the study showed that for a better management of avian collibacillosis in Benin, the tetracolivit is suitable as antibiotic which can be substituted by Aeollanthus pubescens essential oils.